Seismic Evaluation of a Multitower Connected Building by Using Three Software Programs with Experimental Verification - Deyuan Zhou; Changtuan Guo; Xiaohan Wu; Bo Zhang (Shock and Vibration)
Shanghai International Design Center (SHIDC) is a hybrid structure of steel frame and reinforced concrete core tube (SF-RCC). It is a building of unequal height two-tower system and the story lateral stiffness of two towers is different, which may result in the torsion effect. To fully evaluate structural behaviors of SHIDC under earthquakes, NosaCAD, ABAQUS, and Perform-3D, which are widely applied for nonlinear structure analysis, were used to perform elastoplastic time history analyses. Numerical results were compared with those of shake table testing. NosaCAD has function modules for transforming the nonlinear analysis model to Perform-3D and ABAQUS. These models were used in ABAQUS or Perform-3D directly. With the model transformation, seismic performances of SHIDC were fully investigated. Analyses have shown that the maximum interstory drift can satisfy the limits specified in Chinese code and the failure sequence of structural members was reasonable. It meant that the earthquake input energy can be well dissipated. The structure keeps in an undamaged state under frequent earthquakes and it does not collapse under rare earthquakes; therefore, the seismic design target is satisfied. The integrated use of multisoftware with the validation of shake table testing provides confidence for a safe design of such a complex structure.